Penetrating abdominal wounds: about 44 observations - Martínez, Martín; Rubio, Roberto; Amorín, Raúl (Cirugía del Uruguay, 2020)
Forty-four cases of perforating abdominal wounds . are reported. Of these, one died in hospital ( 2,2 % ) , and two following a long term course of 3 and 8 month, respectively. The complication and causes underlying these fatal outcomes are discussed. Resucitation measures, operative timeliness, approach and technique, as well as post operative management, are dealt with.